Analisis Tingkat Intensitas Membaca Al-Qur’an Terhadap Kesehatan Mental Pada Mahasiswa/i UIN Siber Syekh Nurjati Cirebon - Aul, Aulia Julianti; Nia Aprilia, Ajeng; Hanirpan, Cahya; Yus Susilowati, Anggi (Departement of PAI, Universitas Majalengka, 2024)
The intensity of a person's reading can influence their reading ability. The most fundamental impact of someone who regularly reads the Quran is that when they face problems, they will attain inner peace and calmness, especially when their soul is in a serene state. This study aims to examine issues among students with varying levels of Quran reading intensity in relation to mental health, and to measure the relationship between the quality or intensity of Quran reading and the mental health levels of students. This research adopts a quantitative approach, specifically descriptive in nature, with data collection conducted through questionnaires created using Google Forms. The data analysis technique employs simple statistical methods with bivariate tests, including formulas such as mean, median, mode, etc. The results of the study revealed that 51.8% of respondents reported that reading the Quran helps them cope with traumatic experiences. This indicates that the Quran plays a significant role as an effective calming mechanism, assisting individuals in processing trauma in a positive way. It can be concluded from this study that reading the Quran significantly contributes to improving mental health.